The prevalence estimates of Mycobacterium bovis infection in cattle with ELISA - BUYUK, F.; BOZUKLUHAN, K.; GULMEZ SAGLAM, A.; GOKCE, G.; CELEBI, O.; CELIK, E.; KIZILTEPE, S.; COSKUN, M. R.; OTLU, S.; SAHIN, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Tuberculosis is an infectious bacterial disease of Bovidae and the causative agent is Mycobacterium bovis. It is responsible for remarkable economic losses among cattle herds with widely dispersion. Prompt and consistent diagnosis of tuberculosis especially in countries where the disease is endemic as in Turkey is of great importance to detect and identify infectious cases for strengthening control measures. In the present study, it was aimed to detect true animal and herd prevalence (within-herd, and between-herd) of antibodies against M. bovis in cattle herds. A serologic survey for antibody detection against the M. bovis was conducted by using an ELISA kit. Thirty three cattle herds were randomly selected from different farms and totally 460 cattle over five years of age were sampled. The true animal, within-herd, and between-herd prevalences found were 5.9% (95% CI = 3.0 to 8.8), 11.1% (95 CI = 6.5 to 15.8) and 73.4% (95 CI = 51.2 to 95.6), respectively. Results will provide useful information about the status of M. bovis infection and will contribute to the disease control practices.